African management principles within the Community Bank. - Keogh, Patrick Gerard (My University, 1996)
The research exposes a developing African Management model, within a case study framework, and deals with its management approach, structures and processes. Through the qualitative research methodology employed sufficient evidence was found to suggest that African Management is (I) eclectic in nature, embracing Lessem's (1990a, 1990b, 1993a, 1993b) constructs of 'Western' empiricism, 'Northern' rationalism, 'Eastern' idealism and 'Southern' humanism in a dynamic whole: (2) that the natural lnclination of organisations and/or sections thereof operating within an environment of collective consciousness is toward a 'Southern' humanistic orientation as opposed to a 'Western' primal, 'Nortnern' rational, or 'Eastern' developmental bias; (3) that such 'Southerness' is pre-eminently concerned with themes of voluntary subordination of self-interest to communal Objectives, rights and obligations, relationships built on trust, community ownership, inclusive and transparent arrangements, democratic decision making processes, celebration, humanistic values, primacy of language and African humility; further to which (4) the pathological down side of over developed 'Southern' humanism - at the expense of 'Western' emplrlcism, 'Northern' rationalism and Eastern' idealism - is heightened expectation, prolonged consultation, favouritism, patronage, and nepotism.
A research report submitted to the Faculty of Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Management (Human Resources).
Keywords: Community banks -- South Africa.; Banks and banking -- South Africa.; Bank management -- South Africa.